(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Nationally and culturally specific units (NCSUs), also referred to as realia or culture-bound terms, are expressions that reflect the cultural life of a community. Because of their embeddedness in local traditions and contexts, they often lack direct equivalents in other languages. This paper outlines the concept and major classifications of NCSUs and examines their implications for translation. The argument advanced is that understanding NCSUs is not only crucial for translation accuracy but also for promoting intercultural understanding and cultural authenticity.